Un enfoque para la evolución de programas en Lenguaje Estructurado mediante Programación Genética - Rojas Galeano, Sergio Andrés; Olarte, Julián Y.; Suárez, David E (Ingeniería, 2008)
Genetic Programming (GP) is an evolutionary computation technique for discovering automatically computer programs, resembling the evolutionary process that follow different species in the Earth. GP have been actively used in a number of applications, most of them using list-processing languages like LISP. Our goal is to run some evolutionary computation experiments using not specialized languages but higher level and more widely used structured languages. For this purpose, a proper computational environment must be developed, so in this paper we present an initial approach for a GP C-based framework.